Change Management: The Higher Education of Islamic University in Indonesia - Mukhtar Mukhtar; Muntholib Muntholib; Bashori Bashori (International Journal of Education, Information Technology, and Others, 2020)
This research aims to find out how the change management process was carried out at the Islamic College in Indonesia, and what was the backgroud changes occur. This research method used qualitative with data collection techniques of interviews, documentation, and observation. The results of this study indicated that the factors driving change were namely; internal and external factors. Internal factors can be arised from within the organization of Islamic higher education institutions. Meanwhile, internal factors can be arised from outside the organization or institution. In the process of change that occurred at UIN Riau and UIN Bandung, Kurt Lewin's theory was more dominated as the main model. However, from the results of this study, the authors resulted in the development of a more dynamic theory of Kurt Lewin, namely (doctrining, unfreezing, changing, freezing, innovating). The five steps of the process of change the researchers produced from an argumentative analysis that changed in nature continue to occur, so that it took various innovations to one another and continuous innovation.